Unity game development cookbook : essential for every game - Buttfield-Addison, Paris, ....-; Manning, Jon, ....-; Nugent, Tim, ....- (Sebastopol : O'Reilly, 2020)
Find out how to use the Unity Game Engine to its fullest for both 3D and 2D game development-from the basics to the hottest new tricks in virtual reality. With this unique cookbook, you'll get started in two ways: First, you'll learn about the Unity game engine by following very brief exercises that teach specific features of the software Second, this tutorial-oriented guide provides a collection of snippets that solve common gameplay problems, like determining if a player has completed a lap in a race Using our cookbook format, we pinpoint the problem, set out the solution, and discuss how to solve your problem in the best and most straightforward way possible so you can move onto the next step in the project. Unity Game Development Cookbook is ideal for beginning to intermediate Unity developers. Beginners will get a broad immersion into the Unity development environment, while intermediate developers will learn how to apply the foundational Unity skills they have to solve real game development problems.
Keywords: Games ; programmeren; Unity (software).